Intermittent inotropic therapy with levosimendan vs. milrinone in advanced heart failure patients. (27th January 2022) - Milwidsky, Assi; Frydman, Shir; Laufer‐Perl, Michal; Sadeh, Ben; Sapir, Orly; Granot, Yoav; Hochstadt, Aviram; Korotetski, Liuba; Ketchker, Liora; Topilsky, Yan; Banai, Shmuel; Havakuk, Ofer
Abstract: Aims: Routine, intermittent inotropic therapy (IIT) is still applied in advanced heart failure (HF) patients either as a bridge to definitive treatment or as a mean to improve quality of life (QOL), despite limited evidence to support its' use. Given recent reports of improved QOL and reduced HF hospitalization, with levosimendan compared with placebo in advanced HF patients, we aimed to assess the effects of switching a small group of milrinone‐treated patients to levosimendan. This was performed as part of a protocol for changing our ambulatory HF clinic milrinone‐based IIT to levosimendan. Methods and results: Single‐centre study of consecutive ambulatory advanced HF patients that received ≥4 cycles of once‐weekly milrinone IIT at our HF outpatient clinic, who were switched to levosimendan IIT. All patients had left ventricular ejection fraction ≤35%, elevated B‐natriuretic peptide (BNP), and were in New York Heart Association Classes III–IV despite maximally tolerated guideline directed medical therapy. Patients were evaluated using BNP levels, echocardiography, cardio‐pulmonary exercise test, and HF QOL questionnaire before and after 4 weeks of levosimendan IIT. The cohort included 11 patients, 10 (91%) were male and the mean age was 76 ± 12 years. After 4 weeks of levosimendan therapy, maximal O2 consumption improved in 8/9 (89%) by a mean of 2.28 mL/kg [95% CI −0.22–3.38, P  = 0.05]. BNP levels decreased in 9/11 (82%) levosimendan treated patients, from a median of 1015 ng/L [261–1035] to 719 ng/L [294–739], ( P  < 0.01). QOL as measure by the EQ‐5D‐5L questionnaire improved in 8/11 (82%) patients after levosimendan IIT, by a median of two points [95% CO −4.14–0.37, P  = 0.09]. On echocardiography, peak systolic annular velocity (S') increased after levosimendan IIT by an average of 3 cm/s [95% CI 0.16–2.10, P  = 0.03]. Conclusions: In this small‐scale study of ambulatory advanced HF patients, we observed improvements in right ventricular systolic function, maximal O2 consumption, and BNP after switching from milrinone to levosimendan based IIT.